Giant adrenocortical carcinoma with 27-month disease-free survival by surgical resection alone: a case report - Straka, Martin; Soumarova, Renata; Bulejcik, Jan; Banik, Martin; Pura, Mikulas; Skrovina, Matej (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
BACKGROUND: Adrenocortical cancer (ACC) is a rare disease with an estimated incidence of 1-2/million/year. The tumour stage and completeness of surgical resection have the biggest impact on survival. Whereas stage I-II patients survive in 55-64% of cases, only 0-5% of patients with stage IV disease are still alive at 5 years. A median survival of 33 months can be expected after curative surgery. Incomplete surgery leads to a significant drop in survival. METHOD: We present a 40-year-old man who underwent a technically demanding complete surgical excision of a giant (26 cm, 2372 g) ACC and experienced a 27-month disease-free survival without any systemic treatment. Detailed description of the surgical anatomy in relation to tumour size and patient body constitution is provided. The surgical strategy and exposure pitfalls under such extreme circumstances are discussed. CONCLUSION: To achieve R0 resection in locally advanced disease, en bloc resection with neighbouring organs is widely recommended. Giant tumours may however pose a technical challenge due to space constraints.
Keywords: přežití bez známek nemoci; dospělí; Disease-Free Survival; lidé; mužské pohlaví; Adrenocortical Carcinoma; staging nádorů; Male; Neoplasm Staging; adrenokortikální karcinom; Adult; Humans